Towards Further Understanding the Role of Curcumin in Wound Healing: A Systems Biology Approach - Anukriti; Dhingra, Naveen; Bhardaj, Ravindra; Bhardwaj, Uma; Dhasmana, Anupam (Letters in Drug Design & Discovery, 2023)
Background: Curcumin, a polyphenolic compound present in the turmeric plant (Curcuma longa) is well known for its anti-aging, anti-tumor, anti-inflammatory, anti-mutagenic and antioxidative properties due to which turmeric has been used as a medicinal plant from ages. Objective: Our current study aims at finding the most potent targets of curcumin displaying efficient binding by using various systems biology tools. Around 560 genes related to wound healing are extracted from PubMed using the combination of words like wound healing, curcumin, Homo sapiens, etc. Methods: For the investigation of the mechanism of curcumin interference at the system level, proteinprotein interaction network (PPIN) of the proteins involved in the wound healing process was generated using the STRING database. The noise of the data generated in PPIN was removed by modulation of the network with the help of Molecular Complex Detection (MCODE) and finding the seed proteins. GO enrichment analysis along with network topology analysis and molecular docking will help in pinpointing the most important and efficient curcumin binding proteins. Results: The findings of this study shows that besides SCR, PPARG and MAPK3, AKT3 is one of the novel targets for wound healing as the binding affinity of AKT3 is -4.53 Kcal/mol, which is close to SRC with the highest binding affinity with binding energy of -6.6 Kcal/mol. The binding energy of PPARG was -6.2 Kcal/mol and for MAPK3 the binding energy was -5.95 Kcal/mol. Besides AKT3, FLT4 and RPS6KB1 were also the novel targets of curcumin with binding affinities of -4.13 Kcal/mol and -4.04 Kcal/mol. In network analysis, we obtained PIK3R1 as a connector node which acted as a hub node with highest betweenness score. Conclusion: From the results obtained, we can say that curcumin finds its role in all four stages of wound healing and it also prevents the healing cells from turning into tumors.
Keywords: AKT3